Pemberdayaan Pemberdayaan Perempuan Muda Muhammadiyah Melalui Kewirausahaan Pupuk Organik Cair (POC) Di PCNA Bumiayu, Jawa Tengah. - Anis Shofiyani; Agus Mulyadi Purnawanto; Hermin Endratno; Hadi Pramono; Totok Haryanto; Fitri Rakhmawati (MALLOMO: Journal of Community Service, 2026)
This community service activity aims to improve the entrepreneurial skills of young Muhammadiyah women, particularly in the production of Liquid Organic Fertilizer (POC), accounting-based financial management, and product packaging and marketing. This program is carried out through training that combines theory and direct practice, where participants are given an understanding of how to conduct POC efficiently, transparent financial management in accordance with accounting standards, and appropriate packaging techniques and marketing strategies to increase product competitiveness. The results of this activity show a significant increase in participant skills, especially in the production of quality POC, more efficient financial management, and more effective product marketing capabilities. The application of science and technology in this activity not only provides technical insight but also strengthens cadres' capacity to address entrepreneurial challenges in the agricultural and environmental sectors.